Effect of Cilostazol Prescribed in a Pragmatic Treatment Program for Intermittent Claudication. (April 2014) - Lee, Constance; Nelson, Peter R.
Background: Controlled trials of cilostazol for claudication demonstrate improvements in walking distance and quality of life. Without the structure of a study environment, it is not certain that cilostazol has similar efficacy. Method: Retrospective review of patients prescribed cilostazol for claudication was undertaken. Patients were advised to stop smoking and increase exercise but no formal programs were instituted. The primary outcome measure was patient-reported improvement in claudication symptoms. Secondary outcomes were smoking cessation and participation in regular exercise. Results: Over a 2-year period, 77 patients were prescribed cilostazol as initial treatment for claudication. Follow-up for 3 months was available for 69 (90%) patients. Noncompliance was reported in 20% of patients. Of the overall group, 58% (73% of compliant patients) of patients reported improvement in claudication symptoms, 4% of patients reported smoking cessation, and 7% reported regular exercise. Conclusion: Despite minimal behavior modification, up to 70% of patients taking cilostazol report an improvement in claudication symptoms with few side effects.